Achieving postoperative target range increases success of strabismus surgery in adults: a case for adjustable sutures?. Issue 12 (19th May 2015) - Mireskandari, Kamiar; Schofield, Jennifer; Cotesta, Melissa; Stephens, Derek; Kraft, Stephen P
Abstract : Background/aims: To evaluate the role of achieving immediate target angles on the success of strabismus surgery. Methods: We performed a retrospective cohort study of all patients over 12 years old undergoing strabismus surgery with either adjustable or non-adjustable sutures. Target angle for patients with esotropia and vertical deviation was within 4 prism dioptres (PD) of orthotropia and for patients with exotropia between orthotropia and 8 PD of esotropia. Success was defined as alignment within 10 PD for horizontal rectus surgery and within 5 PD of orthotropia for vertical rectus surgery, without diplopia or reoperations. The main outcome measure was surgical success rate. Results: Three hundred and fifty-three patients were included in the study with mean follow-up of 13.9 (4–132) months. Patients achieving the target angle immediately postoperatively had higher success rate than patients who did not (83.6% vs 63.7%, p<0.0001, OR 2.9, 95% CI 1.8 to 4.9). When target angle was achieved, adjustable and non-adjustable sutures had similar success (84.8% and 80.9%, respectively, p=0.46, OR 1.3, CI 0.58 to 2.9). However, patients undergoing adjustable surgery were more likely to obtain the target angle (75.5% vs 54%, p<0.0001, OR 2.7, CI 1.7 to 4.2). Success for exotropia surgery was significantly higher when the immediate target angle was achieved (86.4% vs 58.7%, p<0.0001, OR 4.47, CI 2.3 to 8.6). For esotropia and vertical deviations, a similar beneficial effect was not shown (p=0.31, OR 1.6, CI 0.65 to 4.0 and p=0.33, respectively). On multiple logistic regressions, sex, amblyopia, binocularity and reoperations were not significant factors in surgical success. Conclusions: Our results suggest that achieving the immediate target angle is the most significant factor in the success of strabismus surgery for exotropia. Adjustable suture surgery results in higher proportion of patients achieving this target angle.